SCIENTIFIC AND THEORETICAL BASIS OF FINANCING HIGHER EDUCATION INSTITUTIONS (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
Today, the development of the higher education system at the level of international standards is considered a necessary condition for moving the country's economy to the path of innovative development. In this article, the results of research on the scientific-theoretical basis of financing of higher education institutions are analyzed.